2017
DOI: 10.19182/bft2016.329.a31308
|View full text |Cite
|
Sign up to set email alerts
|

Effet Des Facteurs Stationnels Sur La Croissance Radiale Et La Réponse Du Pin D’alep Au Climat Dans Le Massif De L’ouarsenis, Algérie

Abstract: Effet des facteurs stationnels sur la croissance radiale et la réponse du pin d'Alep au climat dans le massif de l'Ouarsenis, Algérie Photo 1. Vue d'ensemble de la zone culminante de l'Ouarsenis où de vastes pinèdes se développent sur substrat calcaire. Photo M. Sarmoum. Correspondance électronique avec les auteurs / Electronic correspondence with authorssarmoum_med@yahoo.fr B O I S E T F O R Ê T S D E S T R O P I Q U E S , 2 0 1 6 , N° 3 2 9 ( 3 ) ABSTRACT EFFECTS OF STATION-SPECIFIC FACTORS ON RADIAL GROWTH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
1
4
0
1
Order By: Relevance
“…Additionally, Olivar et al (2015) found that the radial growth of Aleppo pine was mainly influenced by rainfall. Similar results have been reported by Sarmoum et al (2016). Camarero et al (2020) studied the effect of environmental factors on the growth of P. halepensis stands and noted that their radial growth is related to the availability of water in the soil during previous wet seasons, namely previous spring and winter (Touchan et al 2017, Choury et al 2017).…”
Section: Radial Growth Of Aleppo Pinesupporting
confidence: 83%
See 2 more Smart Citations
“…Additionally, Olivar et al (2015) found that the radial growth of Aleppo pine was mainly influenced by rainfall. Similar results have been reported by Sarmoum et al (2016). Camarero et al (2020) studied the effect of environmental factors on the growth of P. halepensis stands and noted that their radial growth is related to the availability of water in the soil during previous wet seasons, namely previous spring and winter (Touchan et al 2017, Choury et al 2017).…”
Section: Radial Growth Of Aleppo Pinesupporting
confidence: 83%
“…Novak et al (2013b) suggested that IADF formation reflects the plasticity of Aleppo pine and its ability to resume cambial activity after summer drought. Sarmoum et al (2016) recorded a high variation in tree ring width among years even within the same stand. De Luis et al (2011) noted that in the young stage, Aleppo pine show great plasticity in wood formation under the effect of drought.…”
Section: Radial Growth Of Aleppo Pinementioning
confidence: 94%
See 1 more Smart Citation
“…Touchan et al (2017) showed that Atlas cedar has positive relationships with winter and spring precipitation and a negative response with spring and summer temperatures. In addition, compared to other species in the study area (Sarmoum et al, 2016;Hibbani et Abdoun, 2018), Atlas cedar growth is closely related to precipitations and appears more sensitive to drought. We found also that populations located at low altitude and/or marl and sandstone substrate are more sensitive to precipitation.…”
Section: Climate-growth Relationshipmentioning
confidence: 77%
“…Cette baisse a marqué davantage la saison pluvieuse qui s'étend de l'hiver au printemps (figure 2b). Elle a entraîné un allongement de la période sèche (figure 2c) et un glissement des étages bioclimatiques vers l'aridité (Sarmoum et al, 2016).…”
Section: Introductionunclassified